Valorização do multilinguismo: um mapeamento e planejamento linguístico escolar em Foz do Iguaçu, PR - Kuerten, Miriam Regina Giongo (2019)
This quantitative and qualitative research aimed to identify the linguistic repertoire of a teaching institution in the city of Foz do Iguaçu, which is located in the triple border between Brazil, Paraguay and Argentina, reflect on what it is to be multilingual and promote reflections for the valorization of languages. In this regard, the languages spoken by students and collegiate at Colégio Vicenino São José in Foz do Iguassu were mapped. The mapping carried out with the teachers was also intended to understand, whether and / or how the linguistic diversity in the college is perceived and whether they had, in their academic formation or later, (in)formation on linguistic policies and language management. The objective was to map the languages present in this context and to reflect on the themes with which this research relates, among them multilingualism and the valorization of languages, for the school is in a border context in which linguistic heterogeneity could be better perceived and valued, which, among other benefits, would also improve the teaching and learning process. In addition, the School's Political Pedagogical Project was also analyzed to understand if and how the school is pedagogically organized to contemplate multilingualism. This research is based on Language Policy, field of knowledge that is connected to actions in favor of diverse linguistic practices. For the analysis of the data generated through the school linguistic mapping, as well as for the theoretical reference, we sought contributions from Altenhofen and Oliveira (2011), Baker (2001), Bortoni-Ricardo (2008), Broch (2014), Coelho 2012), García (2009), Oliveira (2018), Seiffert (2014), Spolsky (2016) and Vasconcellos (2004) among other authors.